A multi-institutional cohort study on risk of sleep disorders in dry eyes patients using TriNetX - Bing-Qi Wu; Hou-Ting Kuo; Alan Y. Hsu; Yi-Ching Shao; Ning-Yi Hsia; Chun-Ting Lai; Hsin Tseng; Chun-Chi Chiang; Chun-Ju Lin; Huan-Sheng Chen; Yu-Hsun Wang; Yi-Yu Tsai; et al. (Scientific Reports)
Abstract To explore the relationship between DED and sleep disorders and examine the impact of DED’s duration on sleep disorders. This multi-institutional, retrospective cohort study used the TriNetX database. We recruited participants with and without DED diagnosis from 2004 to 2023. Dry eye patients were propensity-matched to individuals from our non-DED cohort (1:1 ratio) based on variables such as age (every 5 year), sex, ethnicity, race, and relevant comorbidities. The Cox proportional hazards regression model was utilized to assess the impact of variables on sleep disorder risk, reporting hazard ratios (HRs) with 95% confidence intervals (CI). Kaplan-Meier survival analysis and log-rank tests were applied to estimate the cumulative incidence of sleep disorder. A total of 688,413 DED adult patients (64.91% female; mean age at index 56.96 ± 15.93) and 688,413 propensity-matched non-DED comparators (64.92% female; mean age at index 56.96 ± 15.93) were recruited. Our analysis showed an overall increased risk of uveitis among DED patients at 5-year time points (HR = 1.04) and all-year (19 years) follow-up durations (HR = 1.03). We observed a higher risk of sleep apnea in DED individuals irrespective of follow-up intervals. Further analyses revealed this increased risk specifically in those diagnosed with Sjögren syndrome (HR = 1.22). This study highlights the significant link between sleep disorders and DED, emphasizing the role of sleep apnea in DED patients. Aqueous-deficient DED has a more pronounced impact on sleep disturbances compared to evaporative DED, while the influence of DED on non-physiological insomnia may be overstated.